Hubungan Fasilitas Bengkel dan Minat Belajar dengan Hasil Belajar Siswa Kelas XI Teknik Pemesinan pada Mata Pelajaran Teknik Pemesinan Frais di SMK Negeri 1 Sumatera Barat - Wifa, Iklil; A, Yufrizal; Syahri, Budi; Afnison, Wanda (TSAQOFAH, 2024)
This study aims to analyze the relationship between workshop facilities and interest in learning with the learning outcomes of students in class XI of Machining Engineering in the Fractional Machining Technique Subject at SMK Negeri 1 West Sumatra. During the lesson, it was found that some workshop facilities were unused and many students lacked the willingness and awareness to follow the lesson well. Students do not fully pay attention to the directions given by the teacher and many students' learning outcomes are low. The type of research used in this study is correlational quantitative research. In this study, the population is class XI students of the Mechanical Engineering Department at SMK Negeri 1 West Sumatra in the 2023/2024 school year. Sampling in this study used the Probability Sampling technique with the Simple random sampling method considering that the population in this study was homogeneous. Based on the research data and the results of the analysis, it can be concluded that between workshop facilities and learning interest in the practical learning process on student learning outcomes in the subject of milling machining techniques at SMK Negeri 1 West Sumatra there is a correlation coefficient of workshop facilities, 0.082 with a significant 0.627 and Learning Interest with the practical learning process on student learning outcomes in the subject of milling machining techniques at SMK Negeri 1 West Sumatra there is a correlation coefficient (r) of 0.312 with a significant 0.056.